68.0k views
1 vote
Find −3a2 − b3 + 3c2 − 2b3 if a = 2, b = −1, and c = 3.

2 Answers

7 votes

Answer:

18

Explanation:

a = 2, b = -1, c = 3

-3a^2 - b^3 + 3c^2 - 2b^3

-3(2^2) - (-1^3) + 3(3^2) - 2(-1^3)

-3(4) - (-1) + 3(9) - 2(-1)

-12 + 1 + 27 + 2

-12 + 30

18 <===

User Elan Hasson
by
5.4k points
2 votes

Answer:

18

Explanation:

-3a² - b³ + 3c² - 2b³

= -3(2)² - (-1)³ + 3(3)² - 2(-1)³

= -3(4) - (-1) + 3(9) - 2(-1)

= (-12 + 1 )+ (27 + 2)

= -11 + 29

= 18

User Eric Fong
by
5.4k points